The Moderating Effect of Subjective Norms on Functional Beverages Purchase Intention - Sosianika, Adila; Kania, Rafiati; Amalia, Fatya Alty (Politeknik Negeri Bandung, 2026)
Young generations in Indonesia have rarely consumed functional beverages, which prominently can improve health status. Promoting healthy beverages is quite challenging in Indonesia. Thus, an understanding of purchasing intention of functional beverages is deemed necessary. Drawing upon the theory of planned behaviour (TPB), this paper proposes a theoretical model portraying the role of attitude, perceived behavioral control, and subjective norms as an interplay factor between purchase intention. In addition, this study also examines the moderating effect of subjective norms toward influencing other factors in purchase intention. A total of 406 valid questionnaires were collected from Generation Y and Z consumers in West Java, Indonesia. The partial least squares structural equation modelling (PLS-SEM) was chosen to analyze the research hypothesis. The results show attitude, subjective norms, and perceived behavioral control directly influence purchase intention. However, only attitude toward purchase intention still negatively influences functional beverage purchase intention. Interesting to note that subjective norms only moderate the attitude of the young generation toward the intention to purchase its beverages. This finding of subjective norms as the moderating effect has emphasized the influence of collectivist cultural setting on Indonesian consumers' healthy consumption.